Sustainable transport for Chinese cities - Mackett, R. L.; May, A. D. (Anthony Dormer), 1944-; Kii, Masanobu; Emerald eBooks (Bingley, U.K. : Emerald, 2013)
The volume is based on papers presented at a workshop on the green transport agenda and its implications for Chinese cities, organised by the World Conference on Transport Research Society in September 2010. The five sections of this volume review the challenges facing urban transport internationally and in China. It considers approaches to policy formulation, the challenge of urban mobility and the development of green sustainable transportation, by reviewing best practice in objective setting, strategy analysis and policy selection, and comparing these with current practice in China. The authors examine passenger transport, and consider a number of current policy interventions in China and compare these with western experience with demand management and new vehicle technologies. Topics include 5D land-use transport model for a high density, rapidly growing city and Contextual requirements for electric vehicles in developed and developing countries. Finally freight and logistics is addressed, including the role of freight villages and milk run strategies, and challenges and policy recommendations for road freight in Shanghai.
Projecting global urbanization and the growth of megacities / Masanobu KII, Kenji Doi -- Implementing sustainable urban travel policies in China / Haixiao Pan -- The three stages of accessibility : the coming challenge of urban mobility / Yves Crozet -- The development of green sustainable transportation in China / Jie Zhao -- Managing urban mobility systems through a cross-assessment model within the framework of land-use and transport integration / Kenji Doi, Masanobu Kii -- Delivering a more sustainable urban environment through transport policy packages / Anthony D. May -- Delivering transport policy change in China : lessons from the UK / Joe Kendal, Marcus Enoch, Stephen Ison -- A 5D land-use transport model for a high density, rapidly growing city / Haixiao Pan -- Reducing car use in urban areas / Roger L. Mackett -- Contextual requirements for electric vehicles in developed and developing countries : the example of China / Wolfgang Schade, Fabian Kley, Jonathan Khler, Anja Peters -- The effectiveness of the construction of the bus rapid transit in Xiamen City / JingWei Bian, Ming Ding -- The integration of the connection between land use and traffic surrounding rail transit stations : the case of Nanjing / Wei Cao, Linbo Qian -- Logistics and the city : the key issue of freight villages / Xiaoming Liu, Michel Savy -- Efficient green logistics in urban areas : milk run logistics in the automotive industry / Toshinori Nemoto, Werner Rothengatter -- The challenges and policy recommendations for road freight in Shanghai / Rong Zhang, Jing Fan, Feng-yuan Zhu -- Conclusions / Anthony D. May, Masanobu Kii, Roger L. Mackett, Haixiao Pan.
Includes index.
Keywords: Urban transportation -- China; Urban transportation -- Environmental aspects -- China; Transportation and state -- China; Sustainable development -- China; Sustainable engineering -- China; Sustainability; Transport planning & policy; Transportation -- General; Transportation -- Automotive -- General; Science -- Environmental Science; Electronic books